Cerebral cortical activation and muscle performance during blood flow restriction training after ischemic stroke: A randomised functional near-infrared spectroscopy study - Xinyu Bai; Yunyun Zhang; Weiwei Cao; Yang Xie; Yonggang Zhu (PLoS ONE, 2025)
Aims To compare the effects of low-load (LL) blood flow restriction (BFR) and high-load (HL) training on cortical activation and the specific contributions of individual brain regions to functional recovery in stroke patients. Methods Sixty-six patients with ischemic stroke were divided into BFR (30% one-repetition maximum [1RM]), matched LL, or HL (80% 1RM) groups. Patients underwent a four-week supervised cycling program, and oxyhemoglobin (HbO) concentrations were assessed during the first session and after the program via functional near-infrared spectroscopy (fNIRS). Muscle performance was characterized by the rectus femoris muscle cross-sectional area (CSA), knee extensor peak torque (PT), and Fugl–Meyer lower extremity (FMLE) scores. Results Compared with the LL group, the BFR and HL groups presented significant brain activation (increased HbO concentration) during the first session (P < 0.05). Following the 4-week intervention, the BFR and HL groups presented greater changes in the HbO concentration (ΔHbO), PT and FMLE scores than did the LL group (P < 0.05). The ΔHbO values in the primary motor cortex (M1), premotor cortex and supplementary motor area (PMC-SMA) of the affected hemisphere (AH) were considerably greater than those in the unaffected hemisphere (P < 0.05), whereas there was no difference in the dorsolateral prefrontal cortex (DLPFC). Changes in PT (mean r = 0.51 [range = 0.46–0.55]; P < 0.05) and FMLE scores (mean r = 0.54 [range = 0.48–0.62]; P < 0.05) were positively correlated with the AH M1 and PMC-SMA ΔHbO across groups. Conclusions and Implications By actively manipulating the M1 and PMC-SMA, LL-BFR and HL training yield comparable short-term improvements in central and peripheral performance after stroke. (Registry: Chinese Clinical Trial Registry; ChiCTR2400087378).